Logistics Innovation in the Medico-Social Sector: An Optimized Workflow for an Efficient Patient Care - Zgaya, Hayfa; Barras, Thomas; Durocher, Alain (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The issue of care for the elderly is a real challenge for our society. The French government offers solutions to users, particularly through institutions hosting for dependent elderly people (nursing homes). We position ourselves in this study in the field of health logistics. We are particularly interested in the implementation of an innovative tool to provide, in real-time, the best possible organization of resources for an efficient patient care. For that, we propose a software solution in the form of a dynamic dashboard, in order to represent and optimize the overall behaviour of a nursing home and especially in terms of resource allocation. This allocation should be in accordance with the workload, patient needs and time constraints. The results show the effectiveness of our solution compared to an intuitive organization based on the experience and the organizational strategies of staff.